AVADAR (Auto-Visual AFP Detection and Reporting): demonstration of a novel SMS-based smartphone application to improve acute flaccid paralysis (AFP) surveillance in Nigeria - Faisal M. B. Shuaib; Philip F. Musa; Sisay Tegegne Gashu; Chima Onoka; Salihu Abdullahi Ahmed; Murtala Bagana; Michael Galway; Fiona Braka; Ticha Johnson Muluh; Richard Banda; Godwin Akpan; Ajiboye Tunji; et al. (BMC, 2018)
Abstract Background Eradication of polio requires that the acute flaccid paralysis (AFP) surveillance system is sensitive enough to detect all cases of AFP, and that such cases are promptly reported and investigated by disease surveillance personnel. When individuals, particularly community informants, are unaware of how to properly detect AFP cases or of the appropriate reporting process, they are unable to provide important feedback to the surveillance network within a country. Methods We tested a new SMS-based smartphone application (App) that enhances the detection and reporting of AFP cases to improve the quality of AFP surveillance. Nicknamed Auto-Visual AFP Detection and Reporting (AVADAR), the App creates a scenario where the AFP surveillance network is not dependent on a limited number of priority reporting sites. Being installed on the smartphones of multiple health workers (HWs) and community health informants (CHIs) makes the App an integral part of the detection and reporting system. Results Results from two phases of tests conducted in Nigeria point to the effectiveness of the App in the surveillance of AFP. Conclusion We posit that appropriate use of the App can soon bring about a worldwide eradication of poliomyelitis.